ECONOMIC ANALYSIS OF OVARIAN HYPOFUNCTION TREATMENTS IN DAIRY COWS IN INDONESIA: A DECISION TREE ANALYSIS - Wicaksono, Ardilasunu; Putro, Krido Brahmo (Universitas Syiah Kuala, 2025)
This study aims to develop an economic model and conduct an analysis to support decision-making among treatment options. To identify the most economically favorable strategy, a decision tree was built to compare the expected monetary value (EMV) of three actions for individual cows. These options were hormone treatment, supportive treatment, and supportive treatment enhanced with management improvements. Additionally, a sensitivity analysis was performed to assess the economic impact of variability in key input parameters. Hormone therapy gave the highest EMV at US989. In contrast, supportive treatment, which is commonly chosen by Indonesian farmers, had the lowest EMV at US925. The combined strategy of supportive treatment with improved management practices offered a higher EMV of US937 compared to supportive treatment alone. In conclusion, hormone therapy yielded the highest EMV, establishing it as the most cost-effective treatment for ovarian hypofunction in cows.